Twenty years of explosive-effusive activity at El Reventador volcano (Ecuador) recorded in its geomorphology - Vallejo, Silvia; Diefenbach, Angela K.; Gaunt, H. Elizabeth; Almeida, Marco; Ramón, Patricio; Naranjo, Fernanda; Kelfoun, Karim (Frontiers in Earth Science, 2024)
Shifts in activity at long-active, open-vent volcanoes are difficult to forecast because precursory signals are enigmatic and can be lost in and amongst daily activity. Here, we propose that crater and vent morphologies, along with summit height, can help us bring some insights into future activity at one of Ecuador’s most active volcanoes El Reventador. On 3 November 2002, El Reventador volcano experienced the largest eruption in Ecuador in the last 140 years and has been continuously active ever since with transitions between and coexistence of explosive and effusive activity, characterized by Strombolian and Vulcanian behavior. Based on the analysis of a large dataset of thermal and visual images, we determined that in the last 20 years of activity, the volcano faced three destructive events: A. Destruction of the upper part of the summit leaving a north-south breached crater (3 November 2002), B. NE border crater collapse (2017), and C. NW flank collapse (2018), with two periods of reconstruction of the edifice: Period 1. Refill of the crater (2002-early 2018) and Period 2. Refill of the 2018 scar (April 2018–December 2022). Through photogrammetric analysis of visual and thermal images acquired in 11 overflights of the volcano, we created a time-series of digital elevation models (DEMs) to determine the maximum height of the volcano at each date, quantify the volume changes between successive dates, and characterize the morphological changes in the summit region. We estimate that approximately 34.1x106 m3 of volcanic material was removed from the volcano due to destructive events, whereas 64.1x106 m3 was added by constructive processes. The pre-2002 summit height was 3,560 m and due to the 2002 eruption it decreased to 3,527 m; it regained its previous height between 2014 and 2015 and the summit crater was completely filled by early April 2018. Event A resulted from an intrusion of magma that erupted violently; we proposed that Events B and C could be a result of an intrusion as well but may also be due to a lack of stability of the volcano summit which occurs when it reaches its maximum height of approximately 3,590 and 3,600 m.